Multiple cerebral abscesses in decompensated cirrhosis of liver as a mimicker of hepatic encephalopathy: A case report (Indian Journal of Case Reports, 2018)
Cirrhosis of the liver is a state of immune dysregulation. It can give way to many infections. Brain abscess, though uncommonly reported in cirrhotic patients, deserves special attention as it presents a diagnostic and therapeutic challenge for physicians. We present here, the case of a 65-year-old diabetic and hypertensive female patient, with cirrhosis of the liver, who presented to us with fever and altered sensorium. She had mild neutrophilic leukocytosis and her serum ammonia level was slightly elevated. She was managed conservatively for hepatic encephalopathy precipitated by infection. No obvious source of infection was found on routine investigation and culture. Broad-spectrum intravenous antibiotic coverage was provided at the earliest, but the patient succumbed to multiorgan failure.